Pelaksanaan Mediasi oleh Kantor Agraria Tata Ruang/Badan Pertanahan Nasional Kabupaten Boyolali Dalam Penyelesaian Sengketa Waris - Ratna Sari Pratiwi; Nanik Sutarni; Muhammad Fauzan Hidayat (Jurnal Bedah Hukum, 2021)
Acquired land questions that are not as per clear arrangements, bringing about irreconcilable circumstances between families. This is known as a "land debate". Land debates are land questions between people, legitimate substances or organizations that don't have an expansive socio-political effect. The goals of this examination are 1) To decide the execution of intercession by the Office of Spatial Agrarian Affairs/National Land Agency of Boyolali Regency in the settlement of legacy debates. 2) Knowing the hindrances in the execution of legacy question settlement intercession by the Office of Spatial Agrarian Affairs/National Land Agency of Boyolali Regency. 3) Knowing the job of an outsider as a go between. The exploration approach utilized in this examination is an observational juridical methodology. This exploration is clear examination. The sort of information utilized is essential information utilizing essential, auxiliary and tertiary legitimate materials. Strategies for gathering information through interviews, documentation, writing study and other inquiries identified with the object of exploration. The information investigation strategy utilized enlightening subjective. The consequences of the exploration are 1) The most common way of carrying out the intervention completed by the Agrarian and Spatial Planning Office/National Land Agency of Boyolali Regency is as per the arrangements in the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency Number 21 of 2020 concerning Handling and Settlement of Land Cases which incorporate : Case study; Initial case title;' Recorded aftereffects of starting case title; Mediation; Final case degree; Minutes of case settlement. Imperatives looked during the time spent carrying out the intervention The shortfall of the respondent and the whereabouts of the litigant is obscure. 3) The Agrarian and Spatial Planning Office/National Land Agency of Boyolali Regency generally includes an outsider in helping the smooth course of intervention. From the consequences of the investigation, it is suggested that the Division of control and treatment of debates in the Agrarian and Spatial Planning Office/Land Agency of Boyolali Regency should lead an assessment after every intercession is completed so the execution of additional intervention can run as expected and agree and harmony between the gatherings. Memperoleh pertanyaan tanah yang tidak sesuai pengaturan yang jelas, membawa situasi yang tidak dapat didamaikan antara keluarga. Ini dikenal sebagai "debat tanah". Debat tanah adalah pertanyaan tanah antara orang-orang, elemen atau yayasan yang sah yang tidak memiliki efek sosial-politik yang luas. Tujuan dari penelitian ini adalah 1) Untuk memutuskan pelaksanaan intervensi oleh Badan Usaha Pertanahan Tata Ruang/Kantor Pertanahan Umum Rezim Boyolali dalam penyelesaian sengketa warisan. 2) Mengetahui hambatan dalam pelaksanaan intervensi penyelesaian debat warisan oleh Badan Penataan Ruang Agraria/Organisasi Pertanahan Umum Rezim Boyolali. 3) Mengetahui pekerjaan orang luar sebagai perantara. Pendekatan pemeriksaan yang digunakan dalam penelitian ini adalah metodologi yuridis observasional. Pemeriksaan ini jelas eksplorasi. Jenis informasi yang digunakan adalah informasi penting yang menggunakan bahan-bahan yang penting, tambahan dan tersier yang halal. Teknik pengumpulan informasi melalui wawancara, dokumentasi, studi penulisan dan kegiatan lain yang diidentifikasi dengan objek eksplorasi. Strategi investigasi informasi yang digunakan jelas subjektif. Akibat dari penyidikan tersebut adalah 1) Cara pelaksanaan intervensi yang paling umum dilakukan oleh Kantor Pertanahan dan Tata Ruang/Kantor Pertanahan Kabupaten Boyolali telah sesuai dengan pengaturan dalam Pedoman Imam Masalah Agraria dan Penataan Ruang/Atas Peraturan Pertanahan Umum Nomor 21 Tahun 2020 tentang Penanganan dan Penyelesaian Perkara Pertanahan yang memuat : Analisis kontekstual; Judul kasus awal;' Efek samping dari rekaman judul kasus yang mendasarinya; Perantaraan; gelar kasus terakhir; Berita acara penyelesaian kasus. Keterbatasan yang dialami dalam siklus syafaat Kekurangan termohon dan keberadaan penggugat tidak jelas. 3) Tempat Kerja Penataan Agraria dan Tata Ruang/Pertanahan Umum Peraturan Daerah Boyolali biasanya melibatkan pihak luar dalam membantu kelancaran siklus intervensi. Dari hasil pemeriksaan, direkomendasikan agar pembagian penguasaan dan perlakuan perdebatan di Kantor Agraria dan Tata Ruang/Kantor Pertanahan Rezim Boyolali harus memimpin penilaian setelah setiap syafaat selesai sehingga dapat dilakukan intervensi lebih lanjut. berjalan sesuai harapan dan sepakat serta harmonis antar pertemuan.